Optimization, stability and characterization of face serum formulation - Buddeen, Mumtaz M. Sultan Suhai (2018)
Nowadays, the demand for skin care products which can give instant beauty effect is increasing rapidly. This has urged some companies to take short cut by incorporating hazardous chemicals into skin care products, consequently caused adverse skin effect over time. Instead, incorporation of face serum into daily skin care routine can give noticeable difference within four weeks. Face serum is a highly concentrated emulsion which consists of small molecules that allow better penetration into the skin thus deliver instant noticeable results. Nevertheless, the stability of face serum formulation needs to be maintained to ensure its effectiveness to the skin. The goal of this study was to determine the optimum and stable face serum formulation with regards to its viscosity and pH value with favourable rheology and sensory characteristics. The formulated face serum was prepared using emulsifiers, thickeners, alpha-mangostin and basic components for skin such as ceramide, amino acids and others. The concentration of emulsifiers and thickeners was optimized using D-optimal mixture design. The independent variables were thickeners (carbopol ultrez 20 and xanthan gum) and emulsifiers (glyceryl stearate and PEG 40 hydrogenated castor oil), while the dependent variables were the viscosity and pH value of the face serum formulations. The study continues in the stability testing concerning on centrifugation, freeze thaw, accelerated stability study and microbiological study. Rheology study was conducted to determine the flow behavior of the face serum. Lastly, 40 respondents was involved in a sensory evaluation test in order to pool public acceptance towards the characteristic of the commercial and formulated face serums. From the study, it was found that the optimum formulation of face serum formulation consists of 0.9% of carbopol ultrez 20, 0.3% of xanthan gum, 0.46% of PEG 40 hydrogenated castor oil and 0.34% of glyceryl stearate. The optimum viscosity and pH value was found to be 4082.65±6.65 cP and 4.56±0.26, respectively. Coefficient of determination (R2) indicated a good fit between the predicted values and the experimental data points. The R2 for viscosity and pH value were found to be 0.9559 and 0.9893, respectively. The stability studies revealed that the optimum formulation exhibits good stability throughout the 90 days of stability testing period as there were no significant change in its viscosity and pH value. Besides, the optimum formulation passed the microbiology test. The optimum formulation shows pseudoplastic Bingham fluid rheology which is the preferred flow behaviour for cosmetic emulsion. Results from the sensory evaluation test revealed that the formulated face serum was able to mimic the characteristics of the commercial face serum since the ANOVA of all attributes showed no significance value. D-optimal mixture design was successful in determining the optimal face serum formulation which is stable with preferred viscosity, pH value, rheology and sensory profile.